Feasibility of using half‐dose Gd‐BOPTA for delayed gadolinium‐enhanced MRI of cartilage (dGEMRIC) at the knee, compared with standard‐dose Gd‐DTPA. Issue 1 (29th May 2019) - Rehnitz, Christoph; Do, Thuy; Klaan, Bastian; Burkholder, Iris; Barié, Alexander; Wuennemann, Felix; Kauczor, Hans‐Ulrich; Weber, Marc‐André
Abstract : Background: We sought to replace full‐dose Gd‐DTPA with safer and lower‐dose contrast agents for delayed gadolinium‐enhanced MRI of cartilage (dGEMRIC). Gd‐BOPTA has a lower intrinsic nephrogenic systemic fibrosis risk and a 2‐fold higher relaxivity at 3T; thus, the contrast agent dose may be halved, further reducing contrast agent‐dependent risks. Purpose: To compare the feasibility of using half‐dose, high‐relaxivity Gd‐BOPTA vs. standard‐dose Gd‐DTPA for dGEMRIC. Study Type: Prospective observational study. Subjects: Eleven healthy volunteers (five women, mean age 25.7 years) and 10 patients with knee pain (three women, mean age 36.7 years; nine with chondromalacia). Field Strength/Sequences: 3D T1 ‐weighted volumetric breath‐hold examination (VIBE) sequence at 3T. Assessment: Knee dGEMRIC was performed twice, first using 0.1 mmol/kg Gd‐BOPTA and 4 weeks later using 0.2 mmol/kg Gd‐DTPA. Contrast penetration was studied using pre‐ and 60–120‐min postcontrast imaging in volunteers and pre‐ and 90‐min postcontrast imaging in patients. Femoral cartilage lesions were assessed using modified whole‐organ MRI scores. Healthy cartilage and partial‐thickness lesions were compared using region‐of‐interest analyses by independent readers. Statistical Tests: Linear mixed‐effect‐models, area under receiver‐operating‐characteristic curve (AUC) analysis, intraclass correlation (ICC). Results: In healthy volunteers, Gd‐BOPTA and Gd‐DTPA T1 ‐values did not differ significantly at any timepoint ( P = 0.164–0.995). In patients, Gd‐BOPTA T1 ‐values (743.33 ± 72.015 msec) were higher than Gd‐DTPA T1 ‐values (681.24 ± 67.635 msec, P = 0.030). Gd‐BOPTA and Gd‐DTPA detected chondromalacia areas equally well, with significantly lower T1 ‐values than in healthy cartilage ( P < 0.001) and nonsignificantly different AUCs (0.92 and 0.96, P = 0.27). The absolute decrease in T1 ‐values between healthy and pathological cartilage was similar (Gd‐BOPTA: 149.59 msec; Gd‐DTPA: 149.44 msec, P = 0.99). ICCs were 0.83–0.98 for Gd‐BOPTA and 0.80–0.98 for Gd‐DTPA. Data Conclusion: Gd‐BOPTA might be used at half the Gd‐DTPA dose in dGEMRIC, with similar contrast penetration and T1 ‐values in healthy cartilage and noninferior detection of cartilage damage. Level of Evidence: 2 Technical Efficacy: Stage 5 J. Magn. Reson. Imaging 2020;51:144–154.